Consuming royal jelly alters several phenotypes associated with overwintering dormancy in mosquitoes - Bianco, Olivia E.; Abdi, Aisha; Klein, Matthias S.; Wei, Xueyan; Sim, Cheolho; Meuti, Megan E. (Frontiers in Insect Science, 2024)
Females of the Northern house mosquito, Culex pipiens, enter an overwintering dormancy, or diapause, in response to short day lengths and low environmental temperatures that is characterized by small egg follicles and high starvation resistance. During diapause, Culex Major Royal Jelly Protein 1 ortholog (CpMRJP1) is upregulated in females of Cx. pipiens. This protein is highly abundant in royal jelly, a substance produced by honey bees (Apis mellifera), that is fed to future queens throughout larval development and induces the queen phenotype (e.g., high reproductive activity and longer lifespan). However, the role of CpMRJP1 in Cx. pipiens is unknown. We first conducted a phylogenetic analysis to determine how the sequence of CpMRJP1 compares with other species. We then investigated how supplementing the diets of both diapausing and nondiapausing females of Cx. pipiens with royal jelly affects egg follicle length, fat content, protein content, starvation resistance, and metabolic profile. We found that feeding royal jelly to females reared in long-day, diapause-averting conditions significantly reduced the egg follicle lengths and switched their metabolic profiles to be similar to diapausing females. In contrast, feeding royal jelly to females reared in short-day, diapause-inducing conditions significantly reduced lifespan and switched their metabolic profile to be similar nondiapausing mosquitoes. Moreover, RNAi directed against CpMRJPI significantly increased egg follicle length of short-day reared females, suggesting that these females averted diapause. Taken together, our data show that consuming royal jelly reverses several key seasonal phenotypes of Cx. pipiens and that these responses are likely mediated in part by CpMRJP1.